2021
DOI: 10.1002/ppul.25601
|View full text |Cite
|
Sign up to set email alerts
|

Chylothorax in the neonate—A stepwise approach algorithm

Abstract: Background Chylothorax in neonates results from leakage of lymph from thoracic lymphatic ducts and is mainly congenital or posttraumatic. The clinical course of the effusion is heterogeneous, and consensus on treatment, timing, and modalities of measures has not yet been established. This review aims to present, along with levels of evidence and recommendation grades, all current therapeutic possibilities for the treatment of chylothorax in neonates. Methods An extensive search of publications between 1970 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…Although it is a rare entity, congenital chylothorax is the most common reason for pleural effusion in neonates, and various treatment strategies have been introduced and implemented ( 146 , 147 ). It has been suggested that LUS should be considered for the diagnosis, monitoring, and follow-up of neonates with congenital chylothorax ( 147 , 148 ).…”
Section: Lus In Other Neonatal Lung Diseasesmentioning
confidence: 99%
“…Although it is a rare entity, congenital chylothorax is the most common reason for pleural effusion in neonates, and various treatment strategies have been introduced and implemented ( 146 , 147 ). It has been suggested that LUS should be considered for the diagnosis, monitoring, and follow-up of neonates with congenital chylothorax ( 147 , 148 ).…”
Section: Lus In Other Neonatal Lung Diseasesmentioning
confidence: 99%
“…CL may lead to decreased blood volume, malnutrition, and a compromised immune system ( 16 ), severely affecting post-operative recovery, prolonging the length of stay (LOS), and even increasing mortality ( 17 , 18 ). Four main clinical treatments are available: medium-chain triglyceride diet (MCT diet) [with or without enteral nutrition (EN)] or low-fat diet, parenteral nutrition (PN), drug therapy (somatostatin such as octreotide), and surgery ( 4 , 19 21 ). However, there is no consensus on the optimal management of CL ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time of publication of our systematic analysis of cases between 1990 and 2018, Rocha et al [ 6 ] published a comparable review including algorithms for both congenital and posttraumatic chylothorax. They state that in case of no response after 1 week of conservative treatment and drainage >10 mL/kg/day or persistent drainage of large volumes (>100 mL per day), for a period of 5 consecutive days or severe metabolic and nutritional complications, which are difficult to control, an invasive approach is recommended.…”
mentioning
confidence: 99%